2018
DOI: 10.1371/journal.pone.0194828
|View full text |Cite
|
Sign up to set email alerts
|

Searching for neurodegeneration in multiple sclerosis at clinical onset: Diagnostic value of biomarkers

Abstract: BackgroundNeurodegeneration occurs during the early stages of multiple sclerosis. It is an essential, devastating part of the pathophysiology. Tools for measuring the degree of neurodegeneration could improve diagnostics and patient characterization.ObjectiveThis study aimed to determine the diagnostic value of biomarkers of degeneration in patients with recent clinical onset of suspected multiple sclerosis, and to evaluate these biomarkers for characterizing disease course.MethodsThis cross-sectional study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 39 publications
(39 reference statements)
0
38
0
Order By: Relevance
“…A number of studies (including 312 PMS patients) have reported that CSF or blood NFL (cNFL/bNFL) is higher in PMS compared to RRMS [4,5,[10][11][12][13][14][15][16][17][18][19], or that it increases more quickly in PMS [20]. Others, however, report that NFL is lower in PMS compared to RRMS [21][22][23] or controls [24]. The majority of studies found no significant difference between disease stages [25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Nfl-associations With Disease Coursementioning
confidence: 99%
“…A number of studies (including 312 PMS patients) have reported that CSF or blood NFL (cNFL/bNFL) is higher in PMS compared to RRMS [4,5,[10][11][12][13][14][15][16][17][18][19], or that it increases more quickly in PMS [20]. Others, however, report that NFL is lower in PMS compared to RRMS [21][22][23] or controls [24]. The majority of studies found no significant difference between disease stages [25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Nfl-associations With Disease Coursementioning
confidence: 99%
“…While CSF has some obvious advantages in CNS disease, its use is often limited by the invasive nature of the procedure that precludes its use as a frequent longitudinal marker. In general, there are strong correlations between NF-L levels in CSF, serum, and plasma [97,101,166,167], but while specificity and sensitivity are high in CSF due to the higher levels of NF-L, sensitivity is often lower in plasma [101,164,166,168] and even lower in serum [97]. Finally, the test methods also affect the results.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that NF-L is elevated in the blood and CSF of newly diagnosed MS patients and that this is correlated with disease severity and prognosis [21,[97][98][99]. NF-L is also elevated during disease activity such as a clinical relapse of new lesions on MRI [100,101]. This makes NF-L an attractive diagnostic biomarker in MS although its specificity does not allow differentiation from MS mimics like neuromyelitis optica spectrum disorders or other neuroinflammatory disorders [102,103].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…57 For example, one database analysis found that men were more likely to have pyramidal, brain stem, and cerebellar relapses, which were associated with worse outcomes; women more commonly had sensory or visual symptoms, which showed better recovery; and older patients had poorer recovery from relapses. 58 Considerable progress has been made in researching the prognostic value of biomarkers of axonal damage and neurodegeneration, such as neurofilament-light chain in CSF or serum, glial fibrillary acidic protein in CSF, and retinal nerve fiber layer thickness on OCT. 59 While the results to date are promising, it is premature to recommend biomarker testing as a guide to clinical decision-making. 60,61 The initial clinical assessment will include a complete patient history, neurological examination and consideration of prognostic factors.…”
Section: Treatment Initiation -Relapsing Msmentioning
confidence: 99%